Improvisação e Mudança Organizacional durante a Implementação de Sistema Integrado de Gestão: a voz do usuário - Nóbrega, Diogo Lins (2009)
Nowadays, the implementation of information systems is a major cause of organizational change. Despite most often focused on the perspective of planning, issues relating to unforeseen changes and actions of improvisation have become important in this area of research and practice. This research aims to analyze, according to the user s perception, if actions based on improvisation during the implementation of an Enterprise Resource Planning (ERP) system do leverage effective changes to a public organization in the Brazilian state of Paraíba, in particular its state-owned water company Cagepa. Furthermore, we looked for organizational change models extant in the academic literature and the user s perception in respect to the importance of information systems (IS). Other research goals were to identify the main changes that are brought about by the implementation of an ERP system and to verify if there was user resistance during implementation. This study was performed from the qualitative perspective of a case study, which is an appropriate method for this type of research. The primary data were extracted from ten semi-structured interviews with users of ERP Pirâmide implemented in Cagepa six years ago. Secondary data were collected from literature and documentary research. Data processing was performed using the qualitative content analysis technique proposed by Gläser e Laudel (2009). Such a method is of a deep interpretative nature, driving the researcher through an intense interpretation and organization of results. The key moment of this method is the extraction phase, where significant information are selected for investigation. The Improvisational Model for Change Management proposed by Orlikowski and Hofman (1997) served as the starting point for choosing the research theme. The research findings sustain the Model and indicate that improvisational actions during IS implementation can foster institutionalized changes to a public organization, like in Cagepa. Moreover, one can see that ISs are important to users and promote significant changes when implemented. We also found that resistance from users and actions of improvisation during the implementation of the system did occur.